Bio-based ethylene-co-vinyl acetate/poly (lactic acid) thermoplastic vulcanizates with enhanced mechanical strength and shape memory behavior. (July 2020) - Zhang, Hai-Chen; Huang, Jintao; Zhao, Peng-Fei; Lu, Xiang
Abstract: With the increasing attention to the shortage of petroleum resources and environmental pollution, it is more urgent to develop new type biomass-derived and bio-degradability polymer materials. In this study, a various of bio-based ethylene-co-vinyl acetate (EVA)/poly (lactic acid) (PLA) thermoplastic vulcanizates (TPVs) with enhanced mechanical strength and shape memory behavior were prepared. The Fourier transform infrared spectroscopy (FTIR), torque rheometer, swelling equilibrium experiments, and thermal gravimetric analysis (TGA) indicate that the EVA component is more aggressive to the active radicals than PLA component, and the improvement of gel content for EVA component is more than that of PLA component. The scanning electronic microscope (SEM) and transmission electron microscopy (TEM) show that the co-continuous structure of EVA/PLA/AD TPV could be well maintained when the TMPTA was introduced into the multicomponent system. Obviously, the results also exhibit that the improvement of mechanical strength and shape memory behavior for EVA/PLA/AD TPV could be attributed to the increased gel content, especially the gel content of EVA component, without changing the crystallization behavior of EVA/PLA/AD TPV. Highlights: High performance EVA/PLA-based TPV was obtained via introducing TMPTA. The obtained EVA/PLA-based TPVs owns obvious co-continuous structure. The EVA component is more aggressive to the active radicals than PLA component. The tensile strength of EVA/PLA-based TPVs is significantly improved by 42.3%. The shape memory behavior of the EVA/PLA-based TPVs was obviously improved.